Multi-principal-element alloy film and preparation method thereof

The preparation of Ta-Hf-W multi-main alloy films through multi-target DC magnetron sputtering technology has solved the problems of insufficient hardness and complex preparation of existing multi-main alloy films, and achieved high hardness and excellent performance materials, suitable for Application under extreme conditions.

CN119287315AActive Publication Date: 2025-01-10NAT INNOVATION INST OF DEFENSE TECH PLA ACAD OF MILITARY SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411213414.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-10
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing multi-main alloy films have insufficient hardness, complex preparation process and high cost, making it difficult to achieve high entropy effect and excellent performance.

Method used

The Ta-Hf-W multi-main alloy film is prepared by multi-target DC magnetron sputtering technology. By adjusting the sputtering power and angle of the target material, the precise control and uniform distribution of components are achieved, and a single-phase body-centered cubic crystal structure is formed. Improve hardness and elastic modulus.

Benefits of technology

A Ta-Hf-W multi-main alloy film with small surface roughness, high hardness and large elastic modulus was obtained. It is suitable for aerospace, defense and chemical fields under extreme service conditions, simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287315A_ABST
    Figure CN119287315A_ABST
Patent Text Reader

Abstract

The invention provides a multi-principal-element alloy film and a preparation method thereof. The multi-principal-element alloy film is composed of Ta, Hf and W according to the equal atomic ratio or the non-equal atomic ratio, and the chemical formula of the multi-principal-element alloy film is TaaHfbWc, wherein a is 30%-50%, b is 15%-35%, c is 30%-45%, and a + b + c = 1. The multi-principal-element alloy film provided by the invention can be obtained through a multi-target direct-current magnetron sputtering film deposition method, and the Ta-Hf-W multi-principal-element alloy film is controllable and uniform in component, good in compactness, small in surface roughness and high in hardness and elastic modulus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alloy materials, and in particular relates to a multi-principal-element alloy film and a preparation method thereof. Background Art

[0002] With the continuous deepening of material research, researchers have found that increasing the "entropy" value of alloys can obtain new alloy systems and improve the comprehensive performance of alloy materials. Multi-principal alloys can significantly increase the "entropy" value of alloy systems and produce many unique physical and chemical properties. Multi-principal alloys are composed of five or more elements with equal atomic ratios or nearly equal atomic ratios. The atomic ratio of each element is between 5% and 35%, and the atoms randomly occupy positions in the lattice. Therefore, multi-principal alloys have four unique effects, namely, the high entropy effect in thermodynamics, the slow diffusion effect in kinetics, the distortion effect in the lattice structure, and the "cocktail" effect in performance. With more in-depth research, it is found that there is no strict definition of multi-principal alloys. Researchers also regard three or four-element alloys as multi-principal alloys. Under the synergistic effect of multiple mechanisms, multi-principal alloys are more likely to form simple body-centered cubic (BCC), face-centered cubic (FCC) or hexagonal close-packed (HCP) solid solution structures. Therefore, multi-principal alloys have many excellent properties, such as higher strength and hardness, excellent oxidation resistance, friction and wear resistance, higher fatigue resistance, higher fracture toughness, better corrosion resistance, etc., becoming very promising functional and structural materials in the fields of national defense, chemical industry, aerospace, etc.

[0003] Multi-principal alloy film is a multi-principal alloy film with high mixing entropy. Multi-principal alloy films have similar characteristics to multi-principal alloy bulks, and even outperform bulk alloys in some properties, such as higher hardness and elastic modulus, smaller surface roughness, etc. High-hardness films can be used as wear-resistant coatings. However, the hardness of NbMoTaW, which is widely studied, is only 16.0 GPa (Feng XB, et al. International Journal of Plasticity, 2017, 95: 264-277), so multi-principal alloy films with higher hardness need to be further developed.

[0004] Magnetron sputtering has the characteristics of high deposition rate, good film quality, controllable performance, good bonding strength with the substrate and few impurities, making it one of the most common methods for preparing thin films. Magnetron sputtering deposition most often adopts the form of single-target sputtering, that is, the sputtering target is a single alloy target. This technology can achieve precise control of the stoichiometric ratio of the film components; but its disadvantage is that the preparation of alloy targets is complicated and the cost is high. With the continuous improvement of the preparation technology level, multi-target magnetron sputtering process has been increasingly applied to the preparation research of multi-principal thin films. Multi-target magnetron sputtering uses multiple pure metal targets or binary alloy targets, which can effectively avoid the complex preparation process of a single alloy target; and by changing the sputtering power of the target, the sputtering time of the target and the angle of the target perpendicular to the center line of the sample stage, a film with diversified components can be prepared, making the film preparation more flexible and conducive to high-throughput screening of film composition and performance. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a multi-principal component alloy film and a preparation method thereof. The multi-principal component alloy film is prepared by multi-target DC magnetron sputtering technology. The number of components of the alloy film is ternary, and it has a single-phase body-centered cubic crystal structure, small surface roughness, and high hardness and elastic modulus performance.

[0006] In a first aspect, the present invention provides a multi-principal alloy film, wherein the multi-principal alloy film is composed of Ta, Hf, W in equal or non-equal atomic ratios, and the chemical formula of the multi-principal alloy film is Ta a Hf b W c ; wherein a is 30% to 50%, b is 15% to 35%, c is 30% to 45%, and a+b+c=1. In the present invention, the multi-principal alloy film is composed of only the main components Ta, Hf and W in an equiatomic or non-equiatomic ratio, and a very small amount of inevitable impurities. When the components of the multi-principal alloy film are composed in a non-equiatomic ratio, the chemical formula Ta a Hf b W c In the formula, a, b and c all represent atomic ratios, and a+b+c=1; the value ranges of a, b and c are 30%~50%, 15%~35%, and 30%~45%, respectively. When the components of the multi-principal alloy film are composed of equiatomic ratios, the chemical formula is TaHfW. The multi-principal alloy film provided by the present invention is obtained by a multi-target DC magnetron sputtering film deposition method. The Ta-Hf-W multi-principal alloy film has controllable and uniform composition, good density, small surface roughness, high hardness and elastic modulus.

[0007] Preferably, the multi-principal alloy film has a single-phase body-centered cubic crystal structure, a surface roughness of 5.40-8.34 nm, a hardness of 16.6-19.4 GPa, and an elastic modulus of 278.1-328.5 GPa.

[0008] In a second aspect, the method for preparing the multi-principal alloy film provided by the present invention comprises performing magnetron sputtering film deposition on a Ta target, an Hf target and a W target at a set sputtering power to obtain a multi-principal alloy film.

[0009] Preferably, the method for preparing the multi-principal alloy film includes:

[0010] Substrate treatment: The substrate was ultrasonically cleaned in anhydrous ethanol, then washed with water and dried, and placed on a sample stage.

[0011] Target setting: Place Ta target, Hf target and W target on three DC sputtering target positions in the deposition chamber, respectively, and adjust the angle of the target perpendicular to the center line of the sample stage and the vertical distance between the target and the substrate, respectively.

[0012] Coating treatment: the vacuum degree of the deposition chamber is pumped to the set condition, and then high-purity argon gas is introduced, the gas flow rate is set, the working pressure of the deposition chamber is adjusted, the substrate is covered with a baffle and the target material is pre-sputtered; then the rotation speed of the substrate is set and the baffle is opened for sputtering coating, and a multi-principal alloy film is obtained according to the set process parameters. In the present invention, Ta, Hf, and W targets are prepared by magnetron sputtering film deposition at a set sputtering power. a Hf b W c A multi-principal alloy film, the Ta-Hf-W multi-principal alloy film is made by multi-target DC magnetron sputtering technology, the alloy film has ternary components, has a single-phase body-centered cubic crystal structure, small surface roughness, and high hardness and elastic modulus performance.

[0013] Preferably, in the substrate processing step, the substrate is a single crystal silicon wafer; preferably, the substrate is P-type single crystal silicon having <100> Crystal structure.

[0014] Preferably, in the target material setting step, the Ta target, Hf target and W target are all high-purity metal blocks with a purity of ≥99.95%, a diameter of 60±10 mm and a thickness of 3~5 mm.

[0015] Further preferably, in the substrate treatment step, the ultrasonic frequency is 60-80 Hz, and the ultrasonic time is 10±5 min; and / or, the smooth surface of the substrate is polished with a damping cloth before ultrasonic cleaning.

[0016] Further preferably, in the target setting step, the angle of the target perpendicular to the center line of the sample stage is 20-40°; the vertical distance between the pure metal block target of Ta, Hf, and W and the substrate is 5-15 cm. Under the same conditions of other preparation parameters, the angle will affect the deposition rate of the film. Too small or too large will affect the thickness of the film. When the angle is 20-40°, the projected area of ​​the target relative to the substrate is relatively large, the deposition rate is relatively fast, and the efficiency is high.

[0017] Preferably, in the coating process, the vacuum degree of the deposition chamber is 6×10 -4 ~8×10 -4 Pa; the working gas pressure is 0.7~0.9 Pa; the inert gas is high-purity argon, the gas flow rate is 30~50 sccm, and the purity is ≥99.999%.

[0018] Further preferably, in the coating treatment step, the sputtering power of the Ta target is 100-150 W, the sputtering power of the Hf target is 50-100 W, the sputtering power of the W target is 100-150 W, the pre-sputtering time is 10-15 min, and the sputtering time is 1±0.2 h. In the present invention, for the sputtering power, when it is lower than the required sputtering power, the target is not easy to glow, and when it is higher than the required sputtering power, it is easy to cause the equipment to overheat and affect the sputtering effect.

[0019] Preferably, the method for preparing the multi-principal component alloy film comprises the following steps.

[0020] 1) Place the substrate in anhydrous ethanol for ultrasonic cleaning to remove pollutants attached to the surface of the substrate, and then rinse the substrate with deionized water.

[0021] 2) Blow dry the cleaned substrate with compressed nitrogen to make the surface of the substrate clean and prevent water stains from remaining.

[0022] 3) Fix the substrate with its smooth surface facing downward on the furnace plate, fix the furnace plate on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition equipment, and rotate the sample stage baffle to adjust it to a position covering the substrate.

[0023] 4) Place Ta, Hf and W metal bulk targets on three different DC target positions in the deposition chamber, respectively, and adjust the angle of each target perpendicular to the center line of the sample stage and the vertical distance between each target and the sample stage.

[0024] 5) Adjust the vacuum degree of the deposition chamber.

[0025] 6) Introduce argon gas into the deposition chamber, adjust the working gas pressure, set the sputtering power of the target material respectively, and pre-sputter the target material.

[0026] 7) Set the rotation rate of the sample stage, open the substrate baffle, and perform sputtering deposition on the smooth surface of the substrate to obtain a thin film.

[0027] 8) Cooling the film to room temperature under vacuum.

[0028] Further preferably, the method for preparing the multi-principal component alloy film comprises the following steps.

[0029] 1) Place the substrate in anhydrous ethanol for ultrasonic cleaning to remove pollutants attached to the surface of the substrate, and then rinse the substrate with deionized water.

[0030] 2) Blow dry the cleaned substrate with compressed nitrogen to make the surface of the substrate clean and prevent water stains from remaining.

[0031] 3) Fix the substrate with its smooth surface facing downward on the furnace plate, fix the furnace plate on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition equipment, and rotate the sample stage baffle to adjust it to a position covering the substrate.

[0032] 4) Place Ta, Hf and W metal bulk targets on three different DC target positions in the deposition chamber, respectively, and adjust the angle of each target perpendicular to the center line of the sample stage and the vertical distance between each target and the sample stage.

[0033] 5) Use a mechanical pump to evacuate the deposition chamber to less than 8.0 Pa, and then use a molecular pump to evacuate the deposition chamber to less than 6.0×10 -4 ~8×10 -4 Pa.

[0034] 6) Introduce argon gas into the deposition chamber, adjust the working gas pressure to 0.7~0.9 Pa, turn on the DC power supply of the corresponding target material, set the sputtering power of the target material respectively, and pre-sputter the target material for 10~15 min; remove impurities such as oxides formed on the surface of the target material through pre-sputtering.

[0035] 7) Set the rotation rate of the sample stage to 15-30 r / min, open the substrate baffle, and perform sputtering deposition on the smooth surface of the substrate for 1±0.2 h to obtain a thin film.

[0036] 8) After the sputtering deposition is completed, the DC power supply is turned off, the argon gas is turned off, the rotation of the sample stage is stopped, the film is cooled to room temperature under vacuum, and then taken out to reduce oxidation contamination, and finally the Ta is obtained on the substrate. a Hf b W c Multi-principal alloy films.

[0037] In a third aspect, the present invention provides applications of the multi-principal alloy film or the multi-principal alloy film obtained by the preparation method, including applications in surface modification of structural materials in the fields of aerospace, national defense, and chemical industry under extreme service conditions.

[0038] The beneficial effects of the present invention are at least: 1. Ta provided by the present invention a Hf b W c The multi-target DC magnetron sputtering technology used in the multi-principal alloy film is a method of co-sputtering of multiple targets, and the target material is a pure metal bulk target material. This method can avoid the complicated target material preparation process, and by changing the sputtering power of the target material or the sputtering time of the target material, multi-principal alloy films with various chemical compositions can be prepared. This method has the characteristics of high deposition rate, wide material applicability, good repeatability, etc. Pure metal targets are used in the preparation process of the present invention, and the raw materials are simple and easy to obtain, which is suitable for large-scale industrial production.

[0039] 2. Ta prepared by the present invention a Hf b W c The elements of the multi-principal alloy film are evenly distributed and have a single-phase body-centered cubic crystal structure. a Hf b W c The multi-principal alloy film not only has higher hardness and elastic modulus, but also has lower surface roughness.

[0040] 3. The elements in the present invention are Ta, Hf and W, which can form a high-hardness multi-principal-element alloy film with a wide range of components.

[0041] 4. Ta provided by the present invention a Hf b W c Multi-principal alloy film, which is made by multi-target DC magnetron sputtering technology, has a surface roughness of 5.40~8.34 nm, a hardness of 16.6~19.4 GPa, an elastic modulus of 278.1~328.5 GPa, and uses a small number of metal elements. It has a broader application prospect and can be used in surface modification of structural materials in extreme service conditions such as aerospace, national defense, chemical industry, etc., to improve the strength, hardness and wear resistance of the material surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 is Ta in Example 1 of the present invention 0.43 Hf 0.14 W 0.43 SEM images of the surface and cross-sectional morphology of multi-principal alloy films.

[0044] Figure 2 is Ta in Example 1 of the present invention 0.43 Hf 0.14 W 0.43 Surface scanning EDS map of elements of multi-principal alloy films.

[0045] Figure 3 is Ta in Example 1 of the present invention 0.43 Hf 0.14 W 0.43 AFM image of the surface morphology of multi-principal alloy films.

[0046] Figure 4 is Ta in Example 1 of the present invention 0.43 Hf 0.14 W 0.43 XRD pattern of multi-principal alloy films.

[0047] Figure 5 is Ta in Example 2 of the present invention 0.50 Hf 0.17 W 0.33 SEM images of the surface and cross-sectional morphology of multi-principal alloy films.

[0048] Figure 6 is Ta in Example 2 of the present invention 0.50 Hf 0.17 W 0.33 Surface scanning EDS map of elements of multi-principal alloy films.

[0049] Figure 7 is Ta in Example 2 of the present invention 0.50 Hf 0.17 W 0.33 AFM image of the surface morphology of multi-principal alloy films.

[0050] Figure 8 is Ta in Example 2 of the present invention 0.50 Hf 0.17 W 0.33XRD pattern of multi-principal alloy films.

[0051] Fig. 9 Surface and cross-sectional SEM images of the TaHfW multi-principal alloy film in Example 3 of the present invention.

[0052] Fig.10 This is a surface scanning EDS image of the elements of the TaHfW multi-principal alloy film in Example 3 of the present invention.

[0053] Fig.11 This is an AFM image of the surface morphology of the TaHfW multi-principal alloy film in Example 3 of the present invention.

[0054] Fig.12 This is the XRD diagram of the TaHfW multi-principal alloy film in Example 3 of the present invention.

[0055] Fig.13 is Ta in Comparative Example 1 of the present invention 0.64 Hf 0.12 W 0.24 SEM images of the surface and cross-sectional morphology of multi-principal alloy films.

[0056] Fig.14 is Ta in Comparative Example 1 of the present invention 0.64 Hf 0.12 W 0.24 Surface scanning EDS map of elements of multi-principal alloy films.

[0057] Fig.15 is Ta in Comparative Example 1 of the present invention 0.64 Hf 0.12 W 0.24 AFM image of the surface morphology of multi-principal alloy films.

[0058] Fig.16 is Ta in Comparative Example 1 of the present invention 0.64 Hf 0.12 W 0.24 XRD pattern of multi-principal alloy films. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] The raw materials used in the following embodiments can all be purchased commercially: the high-purity Ar gas used in the present invention is purchased from Beijing Qianxi Jingcheng Gas Co., Ltd., with a purity greater than or equal to 99.999%. The Ta, Hf and W target materials used in the thin film prepared by the present invention are all commercially available products with a purity greater than or equal to 99.95%, and the crystalline silicon wafer is a commercially available commodity. The high vacuum magnetron sputtering coating equipment used in the thin film prepared by the present invention is a magnetron sputtering coating equipment produced by Shenyang Scientific Instrument Co., Ltd., Chinese Academy of Sciences; the mechanical pump and molecular pump are both supporting equipment of the high vacuum magnetron sputtering coating equipment produced by the same company.

[0061] Example 1 Ta 0.43 Hf 0.14 W 0.43 Preparation of multi-principal alloy films

[0062] The commercial P-type, crystal orientation <100> The single crystal silicon wafer was treated with damping polishing, and then ultrasonically cleaned at a frequency of 60-80 Hz in anhydrous ethanol for 10 min to remove impurities and contaminants attached to the surface of the substrate. The substrate was then rinsed with deionized water and then blown dry with compressed nitrogen to prevent residual water stains on the surface. The smooth surface of the substrate was fixed on the furnace plate with the furnace plate facing down, and the furnace plate was fixed on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition system equipment. The rotating sample stage baffle was adjusted to a position that completely covered the substrate. The metal targets Ta, Hf and W were placed on three different DC target positions in the deposition chamber respectively, and the angles of each metal target perpendicular to the center line of the sample stage were adjusted to 30°, and the vertical distance between the metal target and the sample stage was adjusted to 10 cm. The deposition chamber was first evacuated to less than 8.0 Pa by a mechanical pump, and then the vacuum degree of the deposition chamber was evacuated to less than 6.0×10 -4 Pa; high-purity argon gas with a purity greater than or equal to 99.999% at a gas flow rate of 40 sccm was introduced into the deposition chamber, the working gas pressure was set to 0.7 Pa, the sputtering power of the Ta target was set to 150 W, the sputtering power of the Hf target was set to 60 W, and the sputtering power of the W target was set to 150 W, and the target was pre-sputtered for 10 min to remove impurities such as oxides attached to the surface of the target; after the pre-sputtering was completed, the sample stage rotation rate was set to 15 r / min, the sample stage baffle was opened, and formal sputtering for 1 h was started; after the sputtering was completed, the DC constant current power supply was turned off, the argon switch was turned off, the sample stage rotation was stopped, and the film was cooled to room temperature in a vacuum state before being taken out to reduce oxidation contamination, and finally the Ta film was obtained on the silicon wafer. 0.43 Hf 0.14 W 0.43 Multi-principal alloy films.

[0063] The chemical composition of the multi-principal alloy film was analyzed using an Oxford X-act energy dispersive spectrometer (EDS, installed on a scanning electron microscope). The surface and cross-sectional morphology SEM images and element surface scanning EDS spectra of the multi-principal alloy film are shown in Figure 2. Figure 1 and Figure 2 As shown: According to the quantitative calculation results of the software, the composition of the multi-principal alloy film is Ta 0.43 Hf 0.14 W 0.43 .

[0064] The Ta was photographed using the Dimension ICON atomic force microscope (AFM) from Bruker GmbH, Germany. 0.43 Hf 0.14 W 0.43 The surface morphology of the multi-principal alloy film was analyzed using the tapping mode with a scanning area of ​​10 μm×10 um. The surface roughness (Ra) of the film was analyzed using NanoScope Analysis software. Figure 3 Shown:Ta 0.43 Hf 0.14 W 0.43 The surface AFM morphology of the multi-principal alloy film is a needle-like structure with a surface roughness of 5.40 nm.

[0065] The surface roughness of the film will affect the wear resistance of the film. The friction coefficient and wear rate of the film generally increase with the increase of surface roughness. This is because the rough surface has a smaller contact area and higher contact pressure, which will lead to a higher friction coefficient and wear loss. Therefore, a smaller surface roughness is conducive to improving the wear resistance of the film.

[0066] The Ta was characterized by a D8 Advance X-ray diffractometer (XRD) from BRUKER AXS GmbH, Germany. 0.43 Hf 0.14 W 0.43 XRD phase analysis of multi-principal alloy films was performed with an operating voltage of 40 kV, an operating current of 40 mA, an X-ray source of Cu-Ka (λ=0.15418 nm) rays, a grazing incidence angle of 1°, a scanning speed of 4° / min, a scanning step of 0.02° / step, and a scanning range of 10° to 90°. The results are shown in Figure 4 According to the lattice diffraction extinction law, it can be determined that the three diffraction peaks marked by black diamonds in the spectrum correspond to the (110), (200) and (211) crystal planes of the BCC structure phase, indicating that Ta 0.43 Hf 0.14 W 0.43 The crystal structure of the multi-principal alloy film is a single-phase body-centered cubic (BCC) structure.

[0067] Since the film is a micro-nanoscale material, its hardness can only be measured using a nanoindenter. Vickers hardness and Rockwell hardness are usually used to measure the hardness of alloy blocks, but cannot be used to measure the hardness of films. Therefore, the Nano Indenter G200 nanoindenter produced by Agilent Technologies was used in the continuous stiffness mode to measure the hardness of Ta. 0.43 Hf 0.14 W 0.43 The hardness of the multi-principal alloy film was tested and the results showed that Ta 0.43 Hf 0.14 W 0.43 The nano-indentation hardness value of the multi-principal alloy film is 19.4 GPa, and the elastic modulus value is 328.5 GPa. It can be used in high-hardness and wear-resistant fields.

[0068] Example 2 Ta 0.50 Hf 0.17 W 0.33 Preparation of multi-principal alloy films

[0069] The commercial P-type, crystal orientation <100> The single crystal silicon wafer was treated with damping polishing, and then ultrasonically cleaned at a frequency of 60-80 Hz in anhydrous ethanol for 10 min to remove impurities and contaminants attached to the surface of the substrate. The substrate was then rinsed with deionized water and then blown dry with compressed nitrogen to prevent residual water stains on the surface. The smooth surface of the substrate was fixed on the furnace plate with the furnace plate facing down, and the furnace plate was fixed on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition system equipment. The rotating sample stage baffle was adjusted to a position that completely covered the substrate. The metal targets Ta, Hf and W were placed on three different DC target positions in the deposition chamber respectively, and the angles of each metal target perpendicular to the center line of the sample stage were adjusted to 30°, and the vertical distance between the metal target and the sample stage was adjusted to 10 cm. The deposition chamber was first evacuated to less than 8.0 Pa by a mechanical pump, and then the vacuum degree of the deposition chamber was evacuated to less than 6.0×10 -4 Pa; high-purity argon gas with a purity greater than or equal to 99.999% at a gas flow rate of 40 sccm was introduced into the deposition chamber, the working gas pressure was set to 0.7 Pa, the sputtering power of the Ta target was set to 150 W, the sputtering power of the Hf target was set to 50 W, and the sputtering power of the W target was set to 110 W, and the target was pre-sputtered for 10 min to remove impurities such as oxides attached to the surface of the target; after the pre-sputtering was completed, the sample stage rotation rate was set to 15 r / min, the sample stage baffle was opened, and formal sputtering for 1 h was started; after the sputtering was completed, the DC constant current power supply was turned off, the argon switch was turned off, the sample stage rotation was stopped, and the film was cooled to room temperature in a vacuum state before being taken out to reduce oxidation contamination, and finally the Ta film was obtained on the silicon wafer. 0.50 Hf 0.17 W 0.33Multi-principal alloy films.

[0070] The chemical composition of the multi-principal alloy film was analyzed using an Oxford X-act energy dispersive spectrometer (EDS, installed on a scanning electron microscope). The surface and cross-sectional morphology SEM images and element surface scanning EDS spectra of the multi-principal alloy film are shown in Figure 2. Figure 5 and Figure 6 As shown: According to the quantitative calculation results of the software, the composition of the alloy film is Ta 0.50 Hf 0.17 W 0.33 .

[0071] The Ta was photographed using the Dimension ICON atomic force microscope (AFM) from Bruker GmbH, Germany. 0.50 Hf 0.17 W 0.33 The surface morphology of the multi-principal alloy film was analyzed using the tapping mode with a scanning area of ​​10 μm×10 μm. The surface roughness (Ra) of the film was analyzed using NanoScope Analysis software. Figure 7 Shown:Ta 0.50 Hf 0.17 W 0.33 The surface AFM morphology of the multi-principal alloy film is a needle-like structure with a surface roughness of 6.52 nm.

[0072] The Ta was characterized by a D8 Advance X-ray diffractometer (XRD) from BRUKER AXS GmbH, Germany. 0.50 Hf 0.17 W 0.33 XRD phase analysis of multi-principal alloy films was performed with an operating voltage of 40 kV, an operating current of 40 mA, an X-ray source of Cu-Ka (λ=0.15418 nm) rays, a grazing incidence angle of 1°, a scanning speed of 4° / min, a scanning step of 0.02° / step, and a scanning range of 10° to 90°. The results are shown in Figure 8 According to the lattice diffraction extinction law, it can be determined that the three diffraction peaks marked by black diamonds in the spectrum correspond to the (110), (200) and (211) crystal planes of the BCC structure phase, indicating that Ta 0.50 Hf 0.17 W 0.33 The crystal structure of the multi-principal alloy film is a single-phase body-centered cubic (BCC) structure.

[0073] Since the film is a micro-nanoscale material, its hardness can only be measured using a nanoindenter. Vickers hardness and Rockwell hardness are usually used to measure the hardness of alloy blocks, but cannot be used to measure the hardness of films. Therefore, the Nano Indenter G200 nanoindenter produced by Agilent Technologies was used in the continuous stiffness mode to measure the hardness of Ta. 0.50 Hf 0.17 W 0.33 The hardness of the multi-principal alloy film was tested and the results showed that Ta 0.50 Hf 0.17 W 0.33 The nanoindentation hardness value of the multi-principal alloy film is 18.6 GPa, and the elastic modulus value is 308.3 GPa.

[0074] Example 3 Preparation of TaHfW multi-principal alloy thin film

[0075] The commercial P-type, crystal orientation <100> The single crystal silicon wafer was treated with damping polishing, and then ultrasonically cleaned at a frequency of 60-80 Hz in anhydrous ethanol for 10 min to remove impurities and contaminants attached to the surface of the substrate. The substrate was then rinsed with deionized water and then blown dry with compressed nitrogen to prevent residual water stains on the surface. The smooth surface of the substrate was fixed on the furnace plate with the furnace plate facing down, and the furnace plate was fixed on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition system equipment. The rotating sample stage baffle was adjusted to a position that completely covered the substrate. The metal targets Ta, Hf and W were placed on three different DC target positions in the deposition chamber respectively, and the angles of each metal target perpendicular to the center line of the sample stage were adjusted to 30°, and the vertical distance between the metal target and the sample stage was adjusted to 10 cm. The deposition chamber was first evacuated to less than 8.0 Pa by a mechanical pump, and then the vacuum degree of the deposition chamber was evacuated to less than 6.0×10 -4 Pa; high-purity argon gas with a purity greater than or equal to 99.999% at a gas flow rate of 40 sccm is introduced into the deposition chamber, the working gas pressure is set to 0.7 Pa, the sputtering power of the Ta target is set to 100 W, the sputtering power of the Hf target is set to 100 W, and the sputtering power of the W target is set to 100 W, and the target is pre-sputtered for 10 min to remove impurities such as oxides attached to the surface of the target; after the pre-sputtering is completed, the sample stage rotation rate is set to 15 r / min, the sample stage baffle is opened, and formal sputtering for 1 h is started; after the sputtering is completed, the DC constant current power supply is turned off, the argon switch is turned off, the sample stage rotation is stopped, the film is cooled to room temperature in a vacuum state and then taken out to reduce oxidation contamination, and finally the TaHfW multi-principal alloy film is obtained on the silicon wafer.

[0076] The chemical composition of the multi-principal alloy film was analyzed using an Oxford X-act energy dispersive spectrometer (EDS, installed on a scanning electron microscope). The surface and cross-sectional morphology SEM images and element surface scanning EDS spectra of the multi-principal alloy film are shown in Figure 2. Fig. 9 and Fig.10 As shown: According to the quantitative calculation results of the software, the composition of the multi-principal component alloy film is TaHfW multi-principal component alloy film.

[0077] The Ta was photographed using the Dimension ICON atomic force microscope (AFM) from Bruker GmbH, Germany. 0.43 Hf 0.14 W 0.43 The surface morphology of the multi-principal alloy film was analyzed using the tapping mode with a scanning area of ​​10 μm×10 um. The surface roughness (Ra) of the film was analyzed using NanoScope Analysis software. Fig.11 As shown: The surface AFM morphology of TaHfW multi-principal alloy film is a needle-like structure with a surface roughness of 8.34 nm.

[0078] The TaHfW multi-principal alloy film was subjected to XRD phase analysis using a D8 Advance X-ray diffractometer (XRD) from BRUKER AXS GmbH, Germany. The operating voltage was 40 kV, the operating current was 40 mA, the X-ray source was Cu-Ka (λ=0.15418 nm), the grazing incidence angle was 1°, the scanning speed was 4° / min, the scanning step was 0.02° / step, and the scanning range was 10° to 90°. The results are shown in the figure. Fig.12 According to the lattice diffraction extinction law, it can be determined that the three diffraction peaks marked by black diamonds in the spectrum correspond to the (110), (200) and (211) crystal planes of the BCC structural phase, indicating that the crystal structure of the TaHfW multi-principal alloy film is a single-phase body-centered cubic (BCC) structure.

[0079] Since the film is a micro-nanoscale material, its hardness can only be measured using a nanoindenter. Vickers hardness and Rockwell hardness are usually used to measure the hardness of alloy blocks, but cannot be used to measure the hardness of films. Therefore, the Nano Indenter G200 nanoindenter produced by Agilent Technologies was used to test the hardness of the TaHfW multi-principal alloy film using the continuous stiffness mode. The results showed that the nanoindentation hardness value of the TaHfW multi-principal alloy film was 16.6 GPa, and the elastic modulus value was 278.1 GPa, which can be used in high-hardness wear-resistant fields.

[0080] Comparative Example 1 Ta 0.64 Hf 0.12 W 0.24 Preparation of multi-principal alloy films

[0081] The commercial P-type, crystal orientation <100> The single crystal silicon wafer was treated with damping polishing, and then ultrasonically cleaned at a frequency of 60-80 Hz in anhydrous ethanol for 10 min to remove impurities and contaminants attached to the surface of the substrate. The substrate was then rinsed with deionized water and then blown dry with compressed nitrogen to prevent residual water stains on the surface. The smooth surface of the substrate was fixed on the furnace plate with the furnace plate facing down, and the furnace plate was fixed on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition system equipment. The rotating sample stage baffle was adjusted to a position that completely covered the substrate. The metal targets Ta, Hf and W were placed on three different DC target positions in the deposition chamber respectively, and the angles of each metal target perpendicular to the center line of the sample stage were adjusted to 30°, and the vertical distance between the metal target and the sample stage was adjusted to 10 cm. The deposition chamber was first evacuated to less than 8.0 Pa by a mechanical pump, and then the vacuum degree of the deposition chamber was evacuated to less than 6.0×10 -4 Pa; high-purity argon gas with a purity greater than or equal to 99.999% at a gas flow rate of 40 sccm was introduced into the deposition chamber, the working gas pressure was set to 0.7 Pa, the sputtering power of the Ta target was set to 180 W, the sputtering power of the Hf target was set to 40 W, and the sputtering power of the W target was set to 80 W, and the target was pre-sputtered for 10 min to remove impurities such as oxides attached to the surface of the target; after the pre-sputtering was completed, the sample stage rotation rate was set to 15 r / min, the sample stage baffle was opened, and formal sputtering for 1 h was started; after the sputtering was completed, the DC constant current power supply was turned off, the argon switch was turned off, the sample stage rotation was stopped, and the film was cooled to room temperature in a vacuum state before being taken out to reduce oxidation contamination, and finally the Ta film was obtained on the silicon wafer. 0.64 Hf 0.12 W 0.24 Multi-principal alloy films.

[0082] The chemical composition of the multi-principal alloy film was analyzed using an Oxford X-act energy dispersive spectrometer (EDS, installed on a scanning electron microscope). The surface and cross-sectional morphology SEM images and element surface scanning EDS spectra of the multi-principal alloy film are shown in Figure 2. Fig.13 and Fig.14 As shown: According to the quantitative calculation results of the software, the composition of the multi-principal alloy film is Ta 0.64 Hf 0.12 W 0.24 Multi-principal alloy films.

[0083] The Ta was photographed using the Dimension ICON atomic force microscope (AFM) from Bruker GmbH, Germany. 0.64 Hf 0.12 W 0.24The surface morphology of the multi-principal alloy film was analyzed using the tapping mode with a scanning area of ​​10 μm×10 um. The surface roughness (Ra) of the film was analyzed using NanoScope Analysis software. Fig.15 Shown:Ta 0.64 Hf 0.12 W 0.24 The surface AFM morphology of the multi-principal alloy film is a columnar structure with a surface roughness of 11.81 nm.

[0084] The Ta was characterized by a D8 Advance X-ray diffractometer (XRD) from BRUKER AXS GmbH, Germany. 0.64 Hf 0.12 W 0.24 XRD phase analysis of multi-principal alloy films was performed with an operating voltage of 40 kV, an operating current of 40 mA, an X-ray source of Cu-Ka (λ=0.15418 nm) rays, a grazing incidence angle of 1°, a scanning speed of 4° / min, a scanning step of 0.02° / step, and a scanning range of 10° to 90°. The results are shown in Fig.16 As shown. 0.64 Hf 0.12 W 0.24 The crystal structure of the multi-principal alloy film is an amorphous structure.

[0085] Since the film is a micro-nanoscale material, its hardness can only be measured using a nanoindenter. Vickers hardness and Rockwell hardness are usually used to measure the hardness of alloy blocks, but cannot be used to measure the hardness of films. Therefore, the Nano Indenter G200 nanoindenter produced by Agilent Technologies was used in the continuous stiffness mode to measure the hardness of Ta. 0.64 Hf 0.12 W 0.24 The hardness of the multi-principal alloy film was tested and the results showed that Ta 0.64 Hf 0.12 W 0.24 The nanoindentation hardness value of the multi-principal alloy film is 12.3 GPa, and the elastic modulus value is 242.6 GPa.

[0086] The properties of the multi-principal alloy thin film materials obtained in the above embodiments and comparative examples are shown in Table 1.

[0087]

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A multi-principal alloy film, characterized in that: The multi-principal alloy film is composed of Ta, Hf, and W in equal or non-equal atomic ratios. The chemical formula of the multi-principal alloy film is Ta a Hf b W c ; Among them, a is 30%~50%, b is 15%~35%, c is 30%~45%, and a+b+c=1.

2. The multi-principal alloy thin film according to claim 1, characterized in that: The multi-principal element alloy film has a single-phase body-centered cubic crystal structure, a surface roughness of 5.40-8.34 nm, a hardness of 16.6-19.4 GPa, and an elastic modulus of 278.1-328.5 GPa.

3. The method for preparing the multi-principal alloy thin film according to claim 1 or 2, characterized in that: The method comprises performing magnetron sputtering film deposition on a Ta target material, an Hf target material and a W target material at a set sputtering power to obtain a multi-principal element alloy film; Preferably, the method for preparing the multi-principal alloy film comprises: Substrate treatment: The substrate was ultrasonically cleaned in anhydrous ethanol, then washed and dried, and placed on a sample stage; Target setting: Place Ta target, Hf target and W target on three DC sputtering target positions in the deposition chamber, and adjust the angle of the target perpendicular to the center line of the sample stage and the vertical distance between the target and the substrate respectively; Coating treatment: evacuate the vacuum degree of the deposition chamber to the set conditions, then introduce high-purity argon gas, set the gas flow, adjust the working gas pressure of the deposition chamber, cover the substrate with a baffle and pre-sputter the target material; then set the rotation speed of the substrate and open the baffle for sputtering coating, and obtain a multi-principal alloy film according to the set process parameters.

4. The method for preparing a multi-principal alloy thin film according to claim 3, characterized in that: In the substrate processing step, the substrate is a single crystal silicon wafer; preferably, the substrate is a P-type single crystal silicon wafer having <100> Crystal structure; and / or, in the target setting step, the Ta target, Hf target, and W target are all high-purity metal blocks with a purity of ≥99.95%, a diameter of 60±10 mm, and a thickness of 3~5 mm.

5. The method for preparing a multi-principal alloy thin film according to claim 4, characterized in that: In the substrate treatment step, the ultrasonic frequency is 60-80 Hz, and the ultrasonic time is 10±5 min; and / or, the smooth surface of the substrate is polished with a damping cloth before ultrasonic cleaning.

6. The method for preparing a multi-principal alloy thin film according to any one of claims 3 to 5, characterized in that: In the target material setting step, the angle of the target material perpendicular to the center line of the sample stage is 20-40°; the vertical distance between the pure metal block target material of Ta, Hf, and W and the substrate is 5-15 cm.

7. The method for preparing a multi-principal alloy thin film according to any one of claims 3 to 6, characterized in that: In the coating process, the vacuum degree of the deposition chamber is 6×10 -4 ~8×10 -4 Pa; the working gas pressure is 0.7~0.9 Pa; the inert gas is high-purity argon, the gas flow rate is 30~50 sccm, and the purity is ≥99.999%.

8. The method for preparing a multi-principal alloy thin film according to claim 7, characterized in that: In the coating treatment step, the sputtering power of the Ta target is 100-150 W, the sputtering power of the Hf target is 50-100 W, the sputtering power of the W target is 100-150 W, the pre-sputtering time is 10-15 min, and the sputtering time is 1±0.2 h.

9. The method for preparing a multi-principal alloy thin film according to any one of claims 3 to 8, characterized in that: The steps include: 1) Place the substrate in anhydrous ethanol for ultrasonic cleaning to remove pollutants attached to the surface of the substrate, and then rinse the substrate with deionized water; 2) Blow the cleaned substrate dry with compressed nitrogen to make the surface of the substrate clean and prevent water stains from remaining; 3) Fix the smooth surface of the substrate on the furnace plate with the surface facing downward, fix the furnace plate on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition equipment, and rotate the sample stage baffle to adjust it to a position covering the substrate; 4) Place Ta, Hf and W metal bulk targets on three different DC target positions in the deposition chamber, respectively, and adjust the angle of each target perpendicular to the center line of the sample stage and the vertical distance between each target and the sample stage; 5) Adjust the vacuum degree of the deposition chamber; 6) Introduce argon gas into the deposition chamber, adjust the working gas pressure, set the sputtering power of the target material respectively, and pre-sputter the target material; 7) Setting the rotation rate of the sample stage, opening the substrate baffle, and performing sputtering deposition on the smooth surface of the substrate to obtain a thin film; 8) Cooling the film to room temperature under vacuum.

10. Use of the multi-principal alloy thin film according to claim 1 or 2 or the multi-principal alloy thin film prepared by the preparation method according to any one of claims 3 to 9, characterized in that: Including applications in surface modification of structural materials in the aerospace, defense, and chemical industries under extreme service conditions.

Citation Information

Patent Citations

  • Nb-Ta-W multi-principal element alloy film and preparation method thereof

    CN114015995A

  • Ultrahigh-temperature high-strength tantalum alloy and preparation method thereof

    CN116676519A